Interspecific variation in the diet of Symphalangus syndactylus and Macaca nemestrina at Genting Highlands, Pahang, Peninsular Malaysia - Roberta Chaya Tawie, Tingga; Millawati, Gani; Nur Azimah, Osman; Nor Rahman, Aifat; Eddie, Chan; Shamsul, Khamis; Emelda Rosseleena, Rohani; Norlinda, Mohd Daut; Abd Rahman, Mohd Ridwan; Badrul Munir, Md Zain (Pensoft Publishers, 2024)
Primate communities in the Genting Highlands consist of a single species of Hylobatidae and four species of Cercopithecidae, which are known to exhibit social interaction behaviour. Thus, a study on the diets of Symphalangus syndactylus (siamang; family Hylobatidae) and Macaca nemestrina (pig-tailed macaque; family Cercopithecidae) was carried out at Genting Highlands, in order to compare the dietary preferences and interspecific competition between the two primate families. A DNA metabarcoding approachwas used to analyse diet intake using non-invasive samples based on the trnL region. Based on the 140 amplicon sequence variants (ASVs) generated, 26 plant orders, 46 different families, 60 genera and 49 species were identified from 23 different plant classes. Fabaceae and Moraceae were classified as the most preferred plants at the family level for S. syndactylus; meanwhile, Piperaceae and Arecaceae were classified as the most preferred for M. nemestrina. Only six out of the 60 different plant genera classified in this study, were found to be consumed by both species. Therefore, the low similarity of preferred plants in the diets between the two families suggests that there is little interspecific competition. These findings are important for future conservation management of highland primates, especially in the Genting Highlands.